Case report of multidisciplinary management of complex pathology of the reproductive system against the background of congenital anomaly of the uterus in combination with surgical pathology - Tysovska, Ivanna; Kurochka , Valentyna (The Ukrainian Scientific Medical Youth Journal, 2025)
this clinical case is an example of successful treatment of complex pathology of the reproductive system against the background of congenital anomaly of the uterus, specifically complete septate uterus with duplicated cervix and longitudinal septum of the upper third of the vagina, in combination with surgical pathology, such as left-sided direct reducible inguinal hernia, using simultaneous surgical intervention with laparoscopic access. No complaints were found during the patient's visit for an annual preventive examination. A full physical, laboratory, and instrumental examination was performed, such as general examination, breast examination and palpation, gynecological examination, including speculum examination and palpation of the pelvic organs, cytomorphological examination of both cervixes, microscopic examination of genital discharge, and transvaginal ultrasound of the pelvic organs. Due to the detection of a mass in the left ovarian region, as well as signs of vulvar lichen sclerosus, additional examination was conducted — ovarian tumor markers (CA 125, HE4, ROMA index) were determined, a Pipelle biopsy of both uterine cavities, a vulvar biopsy, and pelvic MRI were performed. Surgical specialists were involved due to the suspected left-sided direct reducible inguinal hernia for a consultation to establish an accurate diagnosis and choose the optimal therapeutic strategy selection. The multidisciplinary approach to the patient's management demonstrated high treatment efficiency using minimally invasive techniques and contributed to a favorable prognosis.